CRITICAL STUDY OF EDUCATIONAL PHILOSOPHY: IMPLEMENTATION OF CHARACTER EDUCATION IN THE PANCASILA STUDENT PROFILE - Parwati, Ni Putu Yuniarika; Suastra, I Wayan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2024)
This research aims to provide an overview of character education through Pancasila student profiles as an effort to prepare Indonesia's golden generation, as well as to determine field conditions related to the implementation of project to strengthen the Pancasila student profile in schools towards the formation of student character in schools. The Pancasila student profile provides opportunities for students to experience knowledge as a process of strengthening character as well as an opportunity to learn from the surrounding environment. The used method is a literature study. This literature review is a study in the form of books, articles, references related to the idealistic foundations of education in Indonesia which can be used as a reference in the implementation of similar research. This research is also carried out to obtain valid and accurate conclusions. It is hoped that this character strengthening can be implemented as early as possible for students so it can create a golden generation with the best quality and character. However, the implementation, especially in schools, is still not optimal and requires ongoing training and mentoring.